MECHANISM OF COCOA SEEDS (Theobroma cacao, L) TO REDUCE THE INFILTRATION OF LYMPHOCYTES IN THE REGIONAL OF TOOTH EXTRACTION OF RATS - Atik Kurniawati; Zainul Cholid; Budi Yuwono (UPT Penerbitan Universitas Jember, 2022)
The act of removing a tooth from the alveolar bone socket is known as tooth extraction. Tooth extraction causes inflammation around the extraction area. Inflammation after tooth extraction will result in an increase in lymphocyte cells. This increase in the number of lymphocytes is too high due to continued inflammation can cause tissue damage around the socket. Cocoa beans contain chemical compounds that have anti-inflammatory and antioxidant properties that can help the post-extraction inflammation process so that wound healing is faster. Objective: to analyze the mechanism of cocoa bean extract (Theobroma cacao, L) on the decrease in the number of lymphocytes in the socket after tooth extraction of male Wistar rats. Methods: including laboratory experimental research with the post-test control group design. The results of the One-way Anova test showed that the number of lymphocytes decreased in all groups with a significant difference (p<0.05). LSD post hoc test results showed that the overall group was significantly different. Results and Conclusions: 8% cocoa bean extract gel (Theobroma Cacao, L) had an effect on reducing the number of lymphocyte cells in the socket after tooth extraction of male wistar rats compared to those not treated. Keywords: Cocoa, lymphocyte, tooth extraction.